Gendering Roman Imperialism
1 online resource
Keywords: For more than fifty years the standard debates about Roman Imperialism were written more or less entirely in terms of male agency, male competition, and male participation. Not only have women been marginalized in these narratives as just so much collateral damage but there has been little engagement with gender history more widely, with the linkages between masculinity and warfare, with the representation of relations of power in terms of gender differentials, with the ways social reproduction entangled the production of gender and the production of empire. This volume explores how we might gender Roman Imperialism.